LO-mode phonon of KCl and NaCl at 300 K by inelastic x-ray scattering measurements and first principles calculations. (7th September 2022) - Togo, Atsushi; Hayashi, Hiroyuki; Tadano, Terumasa; Tsutsui, Satoshi; Tanaka, Isao
Abstract: Longitudinal-optical (LO) mode phonon branches of KCl and NaCl were measured using inelastic x-ray scattering (IXS) at 300 K and calculated by the first-principles phonon calculation with the stochastic self-consistent harmonic approximation. Spectral shapes of the IXS measurements and calculated spectral functions agreed well. We analyzed the calculated spectral functions that provide higher resolutions of the spectra than the IXS measurements. Due to strong anharmonicity, the spectral functions of these phonon branches have several peaks and the LO modes along Γ–L paths are disconnected.